Potential role of honey in learning and memory - Zahiruddin, Othman; Rahimah, Zakaria; Nik Hazlina, Nik Hussain
The composition and physicochemical properties of honey are variable depending on its floral source and often named according to the geographical location. The potential medicinal benefits of Tualang honey, a multifloral jungle honey found in Malaysia, have recently been attracting attention because of its reported beneficial effects in various diseases. This paper reviews the effects of honey, particularly Tualang honey, on learning and memory. Information regarding the effects of Tualang honey on learning and memory in human as well as animal models is gleaned to hypothesize its underlying mechanisms. These studies show that Tualang honey improves morphology of memoryrelated brain areas, reduces brain oxidative stress, increases brain-derived neurotrophic factor (BDNF) and acetylcholine (ACh) concentrations, and reduces acetylcholinesterase (AChE) in the brain homogenates. Its anti-inflammatory roles in reducing inflammatory trigger and microglial activation have yet to be investigated. It is hypothesized that the improvement in learning and memory following Tualang honey supplementation is due to the significant improvement in brain morphology and enhancement of brain cholinergic system secondary to reduction in brain oxidative damage and/or upregulation of BDNF concentration. Further studies are imperative to elucidate the molecular mechanism of actions.